Evaluating the Effectiveness of the Teaching at the Right Level (TaRL) Approach on Fourth-Grade Students' Email Writing Skills at SDN Lawanggintung 2 - Teti Rostikawati; Ismail Ismail; Elnita Nababan; Reza Fara Nuraziza (Journal of General Education and Humanities, 2025)
This article examines the impact of the Teaching at the Right Level (TaRL) approach on the academic performance of fourth-grade students at SDN Lawanggintung 2. This study is quantitative with a pre-experimental design, using purposive random sampling and a one-group pretest-posttest method. The subjects of this study were fourth-grade students at SDN Lawanggintung 2. The study results showed that the TaRL approach was proven effective in improving the learning outcomes of fourth-grade students of SDN Lawanggintung 2. The research instrument used was the students' pretest and posttest scores in Indonesian, which functioned as a measure of learning outcomes. The pretest results showed an average score of 56.25. After the TaRL approach was applied as a treatment, the post-test results showed an increase in the average score of 78.25. This increase was supported by the significance values ​​of the pretest and posttest, which were <0.05. Furthermore, the N-Gain value 1.61 was included in the high category (g ≥ 0.70), indicating an effective increase. The results suggest that implementing the TaRL approach can notably enhance students' learning achievements in Indonesian language classes.